Effect of promotion and service quality regarding purchasing decisions at the Pradana Honda Dealer Sawangan Branch - Budiman, Surya; Sulaeman, Asep; Shahara, Valeria (Journal of Economics and Business Letters, 2023)
This research aims to determine the influence of promotions and service quality on purchasing decisions at the Sawangan Branch Honda Pradana Dealer. The method used is quantitative. This data collection technique uses the solving formula, and the sample obtained in this study was 77 respondents from consumers of the Honda Pradana Dealer, Sawangan Branch. The research results show that promotions partially influence purchasing decision variables. Service quality partially influences purchasing decision variables. Promotion and service quality simultaneously influence purchasing decisions. The results of this research suggest that the Honda Pradana Dealer, Sawangan Branch, should provide attractive discounts to customers so that customers will feel satisfied. Apart from that, the Honda Pradana Dealer, Sawangan Branch, provides excellent training to its employees to give more attention to customers. Next, the Honda Pradana Branch Dealer. Sawangan provides discounts to promote its products further and notifies customers of new products on social media so they are interested in buying them.